Endovascular Selective Intra-Arterial Infusion of Mesenchymal Stem Cells Loaded With Delta-24 in a Canine Model. Issue 1 (23rd November 2020) - Srinivasan, Visish M; Gumin, Joy; Camstra, Kevin M; Collins, Dalis E; Chen, Melissa M; Shpall, Elizabeth J; Parker Kerrigan, Brittany C; Johnson, Jeremiah N; Chen, Stephen R; Fueyo, Juan; Gomez-Manzano, Cande; Lang, Frederick F; et al.
Abstract: BACKGROUND: Delta-24-RGD, an oncolytic adenovirus, shows promise against glioblastoma. To enhance virus delivery, we recently demonstrated that human bone marrow-derived mesenchymal stem cells loaded with Delta-24-RGD (hMSC-D24) can eradicate glioblastomas in mouse models. There are no studies examining the safety of endovascular selective intra-arterial (ESIA) infusions of MSC-D24 in large animals simulating human clinical situations. OBJECTIVE: To perform canine preclinical studies testing the feasibility and safety of delivering increasing doses of hMSCs-D24 via ESIA infusions. METHODS: ESIA infusions of hMSC-D24 were performed in the cerebral circulation of 10 normal canines in the target vessels (internal carotid artery [ICA]/P1) via transfemoral approach using commercially available microcatheters. Increasing concentrations of hMSC-D24 or particles (as a positive control) were injected into 1 hemisphere; saline (negative control) was infused contralaterally. Toxicity (particularly embolic stroke) was assessed on postinfusion angiography, diffusion-weighted magnetic resonance imaging, clinical exam, and necropsy. RESULTS: ESIA injections were performed in the ICA (n = 7) or P1 (n = 3). In 2 animals injected with particles (positive control), strokes were detected by all assays. Of 6 canines injected with hMSC-D24 through the anterior circulation, escalating dose from 2 × 10 6 cells/20 mL to 1 × 10 8 cells/10 mL resulted in no strokes. Two animals had ischemic and hemorrhagic strokes after posterior cerebral artery catheterization. A survival experiment of 2 subjects resulted in no complications detected for 24-h before euthanization. CONCLUSION: This novel study simulating ESIA infusion demonstrates that MSCs-D24 can be infused safely at least up to doses of 1 × 10 8  cells/10 mL (10 7 cells/ml) in the canine anterior circulation using commercially available microcatheters. These findings support a clinical trial of ESIA infusion of hMSCs-D24.